Overview of Sleep Quality in Elementary School Children with Online Game Addiction - Pebriana, Tika Rifa Luthfiyah; Sutini, Titin; Setyorini, Dyah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Excessive use of online games can lead to online game addiction behavior. This affects the circadian rhythm and the quality of sleep you will have. Poor sleep quality will affect children's growth and development. The purpose of this study was to determine the description of sleep quality in children with online game addiction at SDN Jati 03. This research is a quantitative descriptive research. The sample of this study was 72 elementary school children with online game addiction with the sampling technique, namely total sampling. This research instrument uses the PSQI questionnaire to assess sleep quality which is translated into Indonesian with the results of the validity test of the calculated r of all items (r = 22) with n = 528 and a reliability test of 0.72. The data analysis used is univariate analysis and the results are displayed in the form of frequency distribution tables. The results of this study found that the majority of elementary school-age children with online game addiction had poor sleep quality, namely 44 children (61.1%) while 28 children (38.9%) had good sleep quality. Special attention is needed to overcome online game addiction behavior and improve.